PENGARUH TERAPI SOCIAL SKILLS TRAINING TERHADAP HARGA DIRI DAN PERILAKU AGRESIF REMAJA DI SMK PERTIWI MOJOKERTO DENGAN PENDEKATAN MODEL INTERPERSONAL PEPLAU - Nurul Mawaddah* Ahsan** Lilik Supriati*** (Universitas Muhammadiyah Jember, 2016)
Adolescence is a developmental period marked by physical changes,cognitive and social that can contribute to the emergence of social problems due tothe lack of social skills. Therefore we need therapy social skills training to improvetheir social competence so that the adolescent self-esteem increased in order tobuild and maintain positive relationships with the surrounding environment andfriends. This study aims to determine the effect of social skills therapy trainning toself-esteem and aggressive behavior of adolescents with interpersonal modelsapproach Peplau. The research design is quasi-experimental pre-post test withcontrol group. The sampling technique is Proportionate Stratified RandomSampling with 26 samples obtained for the treatment group and 26 samples for thecontrol group. the results showed that the therapy social skills training andcounseling can improve self-esteem and decrease aggressive behavior. the resultsshowed an increase in self-esteem and a decrease in aggressive behavior in thegroup receiving social skills training therapy were significantly higher (pvalue0.05) compared with the control group. In addition there was no associationfound between self-esteem and aggressive behavior of adolescents. Peplauapproach will make it easier to interact with aggressive adolescents so that therapyis more effective SST.